Seismic Response Analysis of Jointed Rock Slope under Pulse-Like Ground Motions - Xijun Jia; Yu Zhang; Ziyi Zhang (Advances in Civil Engineering)
Because of the forward directivity effects, energy concentration, and fling step effect of pulse-like ground motions, it is easy to cause landslide of jointed rock slope. To reveal the progressive failure mechanism of jointed rock slope under pulse-like ground motions, a 3D discrete element numerical model of jointed rock slope in the northern Yunnan province was established to analyze the acceleration, dynamic displacement, and failure modes under bidirectional pulse-like ground motions. The results show that the time of peak acceleration and peak displacement of the slope are consistent with the peak pulse velocity, and the predominant frequency is also the same. The peak dynamic displacement of the jointed rock slope is about 5–6 cm, but the maximum residual displacement is only 11.3% of the peak dynamic displacement. In the progressive failure process, the displacement first appears at the slope toe, then the fractures in the slope crest are opened, and the rock blocks slide along the bottom surface. The failure mode is tension failure of fractures and block slip.